Mempelajari Faktor-Faktor yang Memengaruhi Efektivitas Kepemimpinan di Perusahaan XYZ - Ahmad Subandi; Edwin Syarip; Erry Nugroho Himawan; Evin Sofianti; Rita Yustika; Widyatmanto Setyawan (Diversity: Jurnal Ilmiah Pascasarjana, 2023)
The Covid-19 pandemic is one of the disruptive elements in this modern era. In addition to the rapid spread, other impacts in the form of progress and increased use of communication technology, especially the internet, require organizations to be able to adapt quickly. For large organizations, of course, is a challenge in itself in the adaptation process. Like other companies, XYZ Company has also been affected by the Covid-19 pandemic. This research tries to study the influence of group and work team behavior factors, leadership model, organizational structure and design, organizational culture, organizational communication, change management and career management on the effectiveness of organizational leadership in XYZ Company. The methodology used in this research is literature study, namely the method in the form of a series of activities related to the methods of collecting library data, reading and taking notes, and managing research materials. The study found that the variables of group and work team behavior, leadership model, organizational structure and design, organizational culture, organizational communication, change management and career management affect the effectiveness of organizational leadership in XYZ Company. It is suggested in further research to study organizational planning variables and their effect on leadership effectiveness.